IMPLEMENTASI PERANGKAP HAMA TENAGA SURYA (LIGHT TRAP) DI DESA BENDUNG - Hakam123, Abdullah; Hadi Putro, Bimo (Conscilience: Jurnal Penelitian dan Pengabdian Masyarakat, 2026)
The implementation program of a solar-powered pest trap (light trap) represents an innovative effort to support environmentally friendly pest control in Desa Bendung. This initiative was motivated by the high intensity of pest attacks on agricultural commodities such as rice, chili, sugarcane, and corn, as well as farmers’ dependence on chemical pesticides. The program was conducted through several stages, including field surveys, tool design, community socialization, trials, evaluation, and assistance. The results indicate that the device effectively attracts and captures pest insects at night while simultaneously improving farmers’ knowledge of simple renewable-energy-based technology. Beyond technical benefits in reducing pest intensity, the program also generated social impacts by increasing awareness of sustainable agriculture. Therefore, the light trap has strong potential as an affordable, practical, and sustainable alternative for rural pest management.